Omejitveni dejavniki pri statični apneji - Koštomaj, Aleš (Šport (Ljubljana), 2017)
Ever since the first deep diving competitions were organized, there has been debate about when the ultimate limits of human apnoeic performance will be reached, and which factors will determine these limits. Divers have thus far surpassed all former predictions by physiologists in depth and time. The common factor for all competitive apnoea disciplines is apnoeic duration, which can be prolonged by any means that increase total gas storage or tolerance to asphyxia, or reduce metabolic rate. These main limiting factors can be broken down further into several physiological or psychophysiological factors, which are identified in this article.
Keywords: breath-hold diving; fiziologija; limiting factors; omejitveni dejavniki; physiology; potapljanje na dih; sport; static apnoea; statična apneja; šport